Climate responsive vernacular architecture: Jharkhand, India - Gautam, Avinash (Kansas State University, 2008)
This research aims to explore and assess passive solar design techniques that promote high thermal comfort in vernacular houses of the state of Jharkhand in India. The study of these houses provides useful insights for designing energy efficient houses that provide thermally comfortable conditions. An analysis of these houses in Ranchi, the capital city of Jharkhand, India provides a context for the field research. Jharkhand predominantly has two different styles of vernacular houses: huts and havelis. These houses were constructed, without any mechanical means, in such a manner as to create micro-climates inside them to provide high thermal comfort levels. Hence the study of thermal comfort levels in these buildings in relation to built environment in today's context is significant. As part of data collection, interviews were conducted with the occupants of ten houses in Ranchi, in June 2007. Two houses of each (huts and havelis) were selected for detailed experimental analysis. Experiment results indicated that all the four selected houses exhibited lower ambient temperature than outside during the day and a higher ambient temperature at night. Brick bat coba and lime mortar were the key materials used for constructing high thermal-mass walls. Adequate ventilation is significant in creating conditions that are comfortable. Aperture to volume ratio of less than 0.051 is not adequate enough to cool the thermal mass of these houses. These houses also use attic space to mitigate the heat gain from the roof. Courtyards and other exterior spaces form an integral part of these houses and influence the thermal conditions in and around the houses. The case studies show that there is a scope for more relaxation of comfort temperature range based on culture and phenomenon of acclimatization. A universal approach in understanding and defining comfort condition fails because the users of these houses were comfortable in conditions defined as uncomfortable by ASHRAE and Nicol.
Keywords: Vernacular architecture; Climate responsive; Thermal comfort; India; Architecture (0729); Energy (0791); Engineering, Environmental (0775)